2021
DOI: 10.3390/agronomy11061022
|View full text |Cite
|
Sign up to set email alerts
|

Capturing GEI Patterns for Quality Traits in Biparental Wheat Populations

Abstract: Genotype-by-environment interaction (GEI) is often a great challenge for breeders since it makes the selection of stable or superior genotypes more difficult. In order to reduce drawbacks caused by GEI and make the selection for wheat quality more effective, it is important to properly assess the effects of genotype, environment, and GEI on the trait of interest. In the present study, GEI patterns for the selected quality and mixograph traits were studied using the Additive Main Effects and Multiplicative Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 51 publications
(79 reference statements)
0
4
0
Order By: Relevance
“…On the other hand, the distinctive and nonrepresentative E6 helped determine specifically adapted genotypes. Therefore, a specifically adapted genotype to a particular environment could be conveniently described by employing this type of graphical representation (Plavsin et al, 2021). Furthermore, closer relationships between test environments showed that the same information could be obtained from fewer environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, the distinctive and nonrepresentative E6 helped determine specifically adapted genotypes. Therefore, a specifically adapted genotype to a particular environment could be conveniently described by employing this type of graphical representation (Plavsin et al, 2021). Furthermore, closer relationships between test environments showed that the same information could be obtained from fewer environments.…”
Section: Discussionmentioning
confidence: 99%
“…It could be possible because some genotypes were more sensitive to changes in the growing environment, while others would be stable in response to the environment. The 'which-won-where' biplot model may be associated with cross-over GEI, ME differentiation, specific adaptation (Gauch and Zobel, 1997;Yan et al, 2000;Yan and Tinker, 2006;Putto et al, 2008, Rao et al, 2011Nehe et al, 2019;Li and He, 2021;Plavsin et al, 2021). Based on the biplot analysis, test environments were divided into three MEs.…”
Section: Discussionmentioning
confidence: 99%
“…However, a few studies have been done on the cultivability and yield stability of these new crops worldwide [ 19 ]. Genotype-by-environment interaction (GEI) is often a great challenge for breeders since it makes the selection of stable or superior genotypes more difficult [ 20 ]. Accurate determination of yield stability of genotypes and quality traits is often difficult owing to the GEI [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Building on the previously discussed analyses, the meticulous examination of the interaction between genotypes and environments on various quality traits like protein content, gluten content, and baking strength across different locations and growing seasons reaffirms the complexity of G × E interactions. This has been a well-established notion in the agronomic literature, as highlighted by Johnson et al [ 51 ] and Plavšin et al [ 52 ]. The observed trends underscore the compelling influence of environmental factors overriding genotypic factors in specific contexts.…”
Section: Discussionmentioning
confidence: 91%